Reaction time measurements under mesopic light levels: Towards estimation of the visual adaptation field. (November 2015) - Cengiz, C; Puolakka, M; Halonen, L
The definition of the visual adaptation field in night-time driving conditions is important to implement the CIE system for mesopic photometry. For this purpose, reaction times to an achromatic circular stimulus appearing at different horizontal and vertical eccentricities were measured on uniform and non-uniform backgrounds under mesopic light levels. A large screen illuminated by three projectors providing a visual field subtending 180° × 44° was used to show the background and stimuli. The results concerning both the uniform and non-uniform fields indicate that reaction times under mesopic light levels depend on the local luminance of the visual task. The location and the luminance of the stimulus and the corresponding background luminance at that point strongly affect the reaction times in mesopic conditions. Luminance distribution of the non-uniform backgrounds also affects visual performance.